Analisis Manajemen Persediaan Pada Produk Minuman Di Kedai Bu Nur Food 18 - Desi Anggraeni; Nafilatul Hikmah; Putri Finanti Ramadhani; Rayi Pranika Sundamanik; Ujang Suherman (Pusat Riset dan Inovasi Nasional, 2024)
UMKM Kedai Bu Nur is a food and coffee shop business located in FOOD 18. However, UMKM Kedai Bu Nur has not implemented good inventory management in running its business. The number of orders for raw materials is only based on estimates and there is no inventory cost calculation. This research aims to find out how Kedai Bu Nur is managed in terms of managing ingredients for beverage sales products in the shop using the EOQ, ROP and maximum inventory methods. Data collection was carried out through documentation, interviews and observation. The results show that the EOQ of Gooday coffee is 85 pack, Luak coffee is 42 pack, pop ice is 28 pack, Indocaffe coffee is 21 pack, ice cubes are 212 balls, sugar is 7 kg, siller is 1 roll. Gooday coffee ROP 14 pack, luak coffee 12 pack, pop ice 12 pack, Indocaffe coffee 12 pack, ice cubes 132 balls, sugar 12 kg, siller 1 roll. Maximum supply of gooday coffee 95 pack, luak coffee 52 pack, pop ice 38 pack, Indocaffe coffee 31 pack, ice cubes 332 balls, sugar 17 kg, siller 2 rolls.